Edukasi Program Fisioterapi Terkait Musculoskeletal Disorder pada Porter di Terminal Tirtonadi Surakarta - Pristianto, Arif; Putri, Rizka Salsabila; Putri, Nuristiqomah Dwi; Fadilah, Yustitya Aprilia Nur; Kurniahadi, Tsania Haifa'; Komalasari, Putri (Warta LPM, 2024)
Musculoskeletal problems are one of the complaints that are often felt by workers, especially people with jobs that require high physical activity (porters). From the results of observations made on the porters at Tirtonadi Terminal, it was found that most of them complained of muscle pain in the area around the shoulders and neck, of course this affects the comfort and productivity of working in the field so that the work carried out is not optimal. The aim of education is to reduce and overcome the pain felt by porters at Tirtonadi Terminal which can be done independently before and after carrying out work. Before providing education, the porters filled out the SPADI questionnaire first to measure the level of pain and difficulties experienced before and after providing education. The method used to provide education was in the form of direct explanations to 20 porters one by one in turn, with delivery media in the form of pamphlets and training simulations. The contents of the pamphlet include doing work exercises before starting work and giving warm water compresses after work. From the results of the education that has been carried out, the results show that many of them apply education regularly, but there are also quite a few porters who do not carry out education regularly. Porters need to be aware of the importance of warming up (work exercises) before doing their work to minimize pain and using warm compresses after work to relieve pain. The physiotherapy educational efforts that have been provided can be accepted and understood easily by the porters so it can be concluded that physiotherapy measures have been proven to reduce and overcome musculoskeletal complaints in Tirtonadi Terminal porters.